Peningkatan Proses dan Hasil Belajar Matematika Menggunakan Model Index Card Match (ICM) di Kelas V SDN 223/II Rantau Embacang - Sintia Sanora; Zulqoidi R Habibie; Opi Andriani (CV. Master Literasi Indonesia, 2025)
This classroom action research (CAR) was conducted to improve the learning process and outcomes of fifth-grade students at SDN 223/II Rantau Embacang through the implementation of the Index Card Match (ICM) model in the topics of decimal numbers and integers. The study was motivated by preliminary observations indicating low student engagement and poor learning outcomes, as shown by learning processes not aligned with the Merdeka Curriculum and daily test scores below the Minimum Competency Criteria (KKTP). The research was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 19 students. Data collection methods included observation and tests, using observation sheets and test instruments. The results showed a significant improvement: the teacher’s performance increased by 25% from Cycle I to Cycle II, reaching 100%; student engagement increased by 50%, reaching 87.5%, surpassing the success indicator of 70%; and student learning outcomes improved from 47% at the initial observation to 75% at the end. In conclusion, the implementation of the ICM model helped actively involve students in the learning process, leading to improved learning outcomes